(untitled) (Student Conference Proceedings, 2025)
Robotic sanding and surface finishing has the potential to help the craft sector to become more productive and more efficient. For small businesses, intuitive programming interfaces are required in order to adopt robotic systems without the need for additional training or personnel. For such an application, we propose an Augmented Reality (AR) system that uses a projector for visualization and a touchscreen-based web interface for input detection. In a user study, the proposed interface is compared to an AR application running on a head-mounted display (HMD). The results indicate that the new approach significantly reduces mental load and increases performance. The combination of projector and touchscreen is generally preferred by the users due to a high intuitiveness and ease of use when compared to the HMD application.